Drug-Induced Exacerbation of BECTS - J Gordon Millichap (Pediatric Neurology Briefs, 2001)
The incidence of drug-induced exacerbation of benign epilepsy with centrotemporal spikes (BECTS) was determined retrospectively in 82 patients examined at the Centre Saint Paul, Marseille, France.